Reparative dentinogenesis at a biological method treatment of pulpitis (Эндодонтия Today)
The article presents the results of morphological study of the 72 pulp of permanent incisors and canines 9 adult mongrel dogs, which was modeled acute focal pulpitis. The obtained histological preparations were stained with hematoxylin and eosin, Mallory and Masson. Result of the study showed that the developed medicinal paste due to the presence in its composition of biologically active metabolites are able to increase the intensity of reparative processes in the pulp of the tooth, while providing anti-inflammatory and antiseptic action. Morphological study of the pulp of teeth of dogs developed in the application of medical pastes showed signs earlier normalization of all structural components of the pulp and accelerating in her reparative processes, in comparison with the control group. Experimental and clinical study of the effect of the paste on the pulp tissue allows to recommend it for treatment of acute focal pulpitis